2018
DOI: 10.1016/j.surg.2018.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open major hepatectomy: a systematic review and meta-analysis of individual patient data

Abstract: Laparoscopic major hepatectomies offer some perioperative advantages, including fewer complications and shorter hospital stay, without increasing the blood loss volume and mortality. Whether these results can anticipate the outcomes in future randomized controlled trials has not been determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
126
2
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(142 citation statements)
references
References 46 publications
9
126
2
5
Order By: Relevance
“…Laparoscopic surgery for hepatobiliary‐pancreatic surgery has also spread quickly over the last decade, with the optimization of procedures and good selection criteria depending on tumor location contributing to improved effectiveness and safety . The merits of laparoscopic surgery in liver resection are thought to be the magnified view and reduced invasiveness of the operation . Compared to open liver resection, in recent reports, less blood loss from the hepatic veins during liver transection contributes to better surgical outcomes with laparoscopic surgery …”
Section: Laparoscopic Liver Resectionmentioning
confidence: 99%
“…Laparoscopic surgery for hepatobiliary‐pancreatic surgery has also spread quickly over the last decade, with the optimization of procedures and good selection criteria depending on tumor location contributing to improved effectiveness and safety . The merits of laparoscopic surgery in liver resection are thought to be the magnified view and reduced invasiveness of the operation . Compared to open liver resection, in recent reports, less blood loss from the hepatic veins during liver transection contributes to better surgical outcomes with laparoscopic surgery …”
Section: Laparoscopic Liver Resectionmentioning
confidence: 99%
“…Laparotomy has long been the preferred surgical approach but laparoscopic liver resection (LLR) is gaining popularity. Advantages of LLR include a quicker recovery and reduced morbidity leading to the consensus that laparoscopy should be considered the standard approach to minor liver resections. However, repeat liver resection is considered a challenging procedure owing to adhesions, anatomical distortion caused by the previous liver resection and other treatment modalities that are often used in the setting of recurrent disease.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the R0 resection rate of LMH group was 96.2%. Recently, some meta-analyses of retrospective studies also observed that no significant difference was found between major LLR and major OLR in the resection margin for HCC patients [24,25]. In order to better learn major LLR for HCC patients, long-term survival rate should also be obtained.…”
Section: Discussionmentioning
confidence: 99%